Estudos computacionais de esfingomielinases D: docking, dinâmica molecular e métodos híbridos QM/MM - Silva, Luciane Sussuchi da [UNESP] (2015)
Sphingomyelinases D (SMase D) are enzymes that catalyze sphingomyelin in ceramida-1-fosfate and choline. This activity is only found in Loxosceles brown spiders and Corynebacterium pathogenic bacterias. SMase D, or phospholipase D, is the main component of spider venoms of the genus Loxosceles, being able to induce the characteristic dermonecrotic features of the whole venom. Despite of the clinical importance o these enzymes, their action mechanism is not completely described. In this work, the catalytic mechanism of SMases D against sphingomyelin is studied through computational methods like docking, classical molecular dynamics, constant pH simulations and hybrid methods QM/MM. First, molecular interactions of SMases D with sulfate ion, myo-inositol-1-phosphate, sphingomyelin (the substrate) and suramin inhibitor are evaluated, as well as the protonation states of the catalytic histidines, 12 and 47, in presence or absence of ligands in the active site. Then, the free energy barrier of 21 kcal/mol for choline release is estimated using the transition state theory and the catalytic constant of Loxosceles laeta activity (kcat). This value is compared to the activation energies obtained through QM/MM simulations for covalent (between 18 and 24 kcal/mol) and non-covalent (25 kcal/mol) pathways. Additionally, the hydroxyl group of sphingomyelin is proposed to play a crucial role in the catalytic mechanism. Depending on the binding way of the hydroxyl group, the catalysis may be covalent or non-covalent, with different reaction products in each case. Interestingly, the two processes showed similar activation energies, suggesting that they may be equally probable, as discussed in some experimental studies for different phospholipase D. Finally, the affinity of SMases for mimetic membranes is discussed